Effect of subcooling and superheating on performance of a cascade refrigeration system with considering thermo- economic analysis and multi-objective optimization - Keshtkar, Mohammad Mehdi (Journal of Advanced Computer Science & Technology, 2016)
In present work, effect of degrees of subcooling and superheating based on thermoeconomic optimization is investigated in two stage-cascade refrigeration system (TS-CRS). At the first step, by using R717 and R744 as refrigerants, a thermoeconomic analysis is applied to TS-CRS. Based on results of the first section and using the genetic algorithm (GA) optimizer implemented in MATLAB, the optimum operative conditions of a specific TS-CRS is determined. Finally, based on the Pareto frontier obtained from the GA optimization, a decision-making strategy is then used to determine a final solution by TOPSIS method. Two single-objective optimization strategies (SOS), i.e. exergetic optimization and cost optimization, are applied on TS-CRS. The aim of the first strategy is to maximize the exergetic efficiency and the aim of the second strategy is minimizing the total annual cost of the system. The case study results show that, compared to the base design, the use of SOS for maximizing of exergetic efficiency can be increases the exergetic efficiency 94.5%. In addition, the use of the second SOS can decrease the total system cost by 11%. Using MOS compared to base design, exergetic efficiency and the total system cost can be increase by 99.1% and 28.6% respectively.